Retrograde recanalisation of popliteal artery occlusion - Mehmet Ali Astarcıoğlu; Taner Şen; Halil İbrahim Durmuş; Basri Amasyalı (KARE Publishing, 2015)
The increasing prevalence of critical lower limb ischemia is frequently associated with complex tibioperoneal obstructive disease and a high rate of amputation. In this article, we report our recent experience in order to highlight this valuable and underutilised technique, which proved successful in a complicated case where a conventional approach failed.